2012
DOI: 10.1002/jclp.21934
|View full text |Cite
|
Sign up to set email alerts
|

Shared Pathogeneses of Posttrauma Pathologies: Attachment, Emotion Regulation, and Cognitions

Abstract: Results suggest that disruption in the ability to regulate emotions is the most consistent predictor of mental health in survivors of interpersonal trauma, followed by cognitions regarding the world, self, and others. Treatment implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…PTSD, depression, and explosive anger. These findings are consistent with previous research that has indicated that emotion dysregulation is associated with PTSD (Amstadter and Vernon, 2008;Kulkarni et al, 2013;Lilly and Hong Phylice Lim, 2013;Tull et al, 2007;Weiss et al, 2012), and depression following exposure to trauma Klemanski et al, 2012;Lilly and Hong Phylice Lim, 2013), and mediates the relationship between exposure to interpersonal trauma and psychological symptoms Stevens et al, 2013). This is also consistent with studies finding that emotion dysregulation is related to anger and aggression (Besharat et al, 2013;Mauss et al, 2007;Memedovic et al, 2010;.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…PTSD, depression, and explosive anger. These findings are consistent with previous research that has indicated that emotion dysregulation is associated with PTSD (Amstadter and Vernon, 2008;Kulkarni et al, 2013;Lilly and Hong Phylice Lim, 2013;Tull et al, 2007;Weiss et al, 2012), and depression following exposure to trauma Klemanski et al, 2012;Lilly and Hong Phylice Lim, 2013), and mediates the relationship between exposure to interpersonal trauma and psychological symptoms Stevens et al, 2013). This is also consistent with studies finding that emotion dysregulation is related to anger and aggression (Besharat et al, 2013;Mauss et al, 2007;Memedovic et al, 2010;.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the relationship between emotion dysregulation and psychopathology appears to be especially prominent in survivors of repeated interpersonal traumatization (Walsh et al, 2011). While the majority of research investigating emotion regulation in trauma survivors has focused on PTSD, there is also evidence that emotion dysregulation contributes to depression in trauma survivors Klemanski et al, 2012;Lilly and Hong Phylice Lim, 2013), as well as in non-trauma exposed individuals (Campbell-Sills et al, 2006;Ehring et al, 2010;Garnefski and Kraaij, 2006). Impairments in emotion regulation have also been linked to anger responses and the perpetration of aggression (Besharat et al, 2013;Mauss et al, 2007;Memedovic et al, 2010;.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lilly and Lim (2013) suggest that influences on women's functioning have been found in the domains of attachment styles, emotional regulation, and cognitions. Attachment style refers to the degree of security an individual feels in close or intimate relationships.…”
Section: Abuse and Woman's Behavioral Functioningmentioning
confidence: 96%
“…This finding is congruent with existing literature. Lilly and Lim (2013) suggested that IPV may lead to emotional deregulation causing inappropriate responses to events and be related to mental health symptoms, such as depression and PTSD.…”
Section: Intersection Of Mental Health and Behavioral Functioning Outmentioning
confidence: 98%